2D Materials Beyond Graphene for Metal Halide Perovskite Solar Cells. Issue 22 (30th July 2018) - Kakavelakis, George; Kymakis, Emmanuel; Petridis, Kostantinos
Abstract: In this Research News, the authors summarize the work that has been done on the utilization of 2D materials beyond graphene in the electron transport layer (ETL) and hole transport layer (HTL) selected of metal halide perovskite solar cells (PSCs). On the one hand, the impact of such materials in the stability of PSCs under operational conditions is impressive. Stabilities for encapsulated PSCs cells under illumination and ambient conditions at maximum power point that retain 80% of their initial performance (T80 ) have been reported. On the other hand, the extraction of photogenerated holes has been reduced to few microsecond when a 2D material–based HTL or ETL is introduced. The faster photogenerated charge extraction lowered the recombination rates and resulted in higher power conversion efficiencies. The most interesting thing is that the 2D materials have been successfully applied for large active area cells (≈1.05 cm 2 ) as well. The exploitation of 2D materials, beyond graphene, is a very interesting and promising technology that shows a high potential pathway towards the envisioned future commercialization of PSCs through addressing their performance, stability, and scalability priorities. Abstract : The impact of transition metal dichalcogendies and black phosphorus 2D layered materials in the performance, stability, and scalability of solution processable perovskite solar cells is summarized in this focused Research News article. These type materials are mainly utilized as HTLs that address very successfully the trade‐off between high conductivity and high stability that their counterparts (organics and GRMs) fail to address.